Anti-Hepatitis C Virus Activity of Various Indonesian Plants from Balikpapan Botanical Garden, East Borneo - Rina Puspitasari; Tutik Sri Wahyuni; Achmad Fuad Hafid; Adita Ayu Permanasari; Lidya Tumewu; Aty Widyawaruyanti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Hepatitis C Virus infection is a serious health problem that leads to chronic liver disease, liver cirrhosis, hepatocellular carcinoma, which causes high morbidity. Direct-Acting Antiviral Agents have been used as anti-hepatitis C Virus therapy. However, it was covered only in limited patients due to the high cost. Moreover, serious side effects and resistance cases were also reported in some HCV genotypes. Objective: This research aimed to find new anti-HCV from some Indonesia plants collected from Balikpapan Botanical Garden, East Borneo. Methods: Twenty-one leaf and stem barks extracts were successively extracted in n-hexane, dichloromethane, and methanol. Extracts were screened for their anti-HCV activity under in vitro culture cells in the concentration of 30 µg/mL. Plant extracts were inoculated in the Human Hepatocellular 7it and infected with HCV Japanese Fulminant Hepatitis strain 1a. Determination of 50% Inhibitory Concentration (IC50) value was further conducted at concentration of 100; 30; 10; 1; 0.1; 0.01 µg/ml of extracts. Results: In vitro anti-HCV activity revealed that among 21 plants extract, 11 extracts, namely, n-hexane extract from Luvunga scandens leaves, DCM extract from the leaf of L. scandens, Artocarpus sericicarpus, Artocarpus dadah, Eusideroxylon zwageri, Neolitsea cassiaefolia, methanol extract from A. sericicarpus and A. anisophyllus leaves, DCM extract from A. anisophyllus and A. elmeri stem bark, methanol extract from A. dadah stem bark, having potential inhibition with IC50 range 0.08 ± 0.05 to 12.01 ± 0.95 µg/mL. Conclusions: These results indicate that the eleven extracts could be good candidates as sources of anti-HCV agents.